2019
DOI: 10.15570/actaapa.2019.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of purpuragenic 595 nm pulsed dye laser versus sequential emission of 595 nm pulsed dye laser and 1,064 nm Nd:YAG laser: a double-blind randomized controlled study

Abstract: Introduction: Erythematotelangiectatic rosacea is a common condition in Caucasians. The most frequently used lasers to treat this condition are pulsed dye laser (PDL) and neodymium:yttrium-aluminum-garnet laser (Nd:YAG). This study compares the treatment efficacy of purpuragenic PDL with that of sequential emission of 595 nm PDL and 1,064 nm Nd:YAG (multiplexed PDL/Nd:YAG). Methods: We performed a prospective, randomized, and controlled split-face study. Both cheeks were treated, with side randomization to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
14
1
1
Order By: Relevance
“…Although six RCT studies implemented the blinding of subjects, the clinicians were not blinded; thus the evaluations of the “Blinding of participants and personnel” for all three included studies were “unclear risk”. Only Alam et al ( 17 ), Campos et al ( 30 ), and Kim et al ( 27 ) reported specific randomization, while the studies by Alam et al ( 17 ) and Seo et al ( 23 )reported allocation concealment. All three studies showed low risks in terms of “detection bias”, “attrition bias”, “reporting bias”, and “other bias”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although six RCT studies implemented the blinding of subjects, the clinicians were not blinded; thus the evaluations of the “Blinding of participants and personnel” for all three included studies were “unclear risk”. Only Alam et al ( 17 ), Campos et al ( 30 ), and Kim et al ( 27 ) reported specific randomization, while the studies by Alam et al ( 17 ) and Seo et al ( 23 )reported allocation concealment. All three studies showed low risks in terms of “detection bias”, “attrition bias”, “reporting bias”, and “other bias”.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies ( 17 , 30 ) reported the pain score of the PDL group, and one study reported the pain score of the Nd:YAG group. Based on the visual analog scale (VAS) as the pain outcome index, the combined result of the PDL group showed a mean (95%CI) = 4.60 (3.17–6.04), indicating not significantly higher ( P = 0.115) pain sensation of patients treated with PDL than that in patients treated with Nd:YAG, mean (95%CI) = 3.07 (1.82–4.32) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…При недостаточно эффективном поглощении кровью для удаления патологического очага требуется многократная обработка (до шести процедур) [28]. При фототермической облитерации микрососудов дермы в области ПГ применение ЛПМ позволяет избежать развития ранних побочных эффектов в виде пурпуры, которые наблюдаются при использовании импульсного лазера на красителе с продолжительностью импульса 450 мкс [29]. Применение неодимового лазера позволило добиться высокой эффективности удаления ПГ, но после его использования у 40% пациентов возникали побочные эффекты в виде рубцевания [17], что связано с фотодеструкцией соединительнотканных компонентов ретикулярного слоя дермы, вследствие проникновения до проксимальной границы дермы ближнего ИК-излучения из-за низкого поглощения кровью.…”
Section: Discussionunclassified
“…Some laser devices combine both PDL and Nd:YAG technology, allowing the firing of the PDL component milliseconds prior to the Nd:YAG wavelength. 37 Some believe that this technique enhances the effectiveness of the Nd:YAG laser by a factor of 3–5 due in part to the transformation of oxyhemoglobin to methemoglobin by the PDL. 37 There has also been a suggestion of reduced purpura in the combined device compared to PDL alone when treating blood vessels.…”
Section: Lasersmentioning
confidence: 99%
“… 37 Some believe that this technique enhances the effectiveness of the Nd:YAG laser by a factor of 3–5 due in part to the transformation of oxyhemoglobin to methemoglobin by the PDL. 37 There has also been a suggestion of reduced purpura in the combined device compared to PDL alone when treating blood vessels. 38 Karsai et al demonstrated, in a split-face randomized study, that use of the dual wavelength PDL-Nd:YAG delivered higher and statistically significant rates of telangiectasia clearance in one treatment that use of a single wavelength PDL or Nd:YAG.…”
Section: Lasersmentioning
confidence: 99%